On mixing and completely mixing properties of positive L^1-contractions of finite real W* -algebras - Rakhimov, A. A.; Akin, H. (Methods of Functional Analysis and Topology, 2010)
We consider a non-commutative real analogue of Akcoglu and Sucheston’s result about the mixing properties of positive L^1-contractions of the L^1-space associated with a measure space with probability measure. This result generalizes an analogous result obtained for the L^1-space associated with a finite (complex) W^*-algebras.